How to Combine Hunger Solutions to Improve their Effectiveness: Building the Framework for a Country Profile Approach - Reuveni, Saada; Czyzewski, Bazyli (Technium Social Sciences Journal, 2022)
Hunger continues to be a major problem in developing countries despite various efforts. Countries with differing socioeconomic profiles, as reflected in their level of development, seem to respond differently to identical programs. The aim of this paper is to therefore propose a new conceptual tool, namely our hunger-management model, which takes into account a country’s developmental level. To investigate the role of a country’s developmental level in making progress in its GHI score over time, data for 124 developing countries were gathered. These countries were divided into two groups according to whether they used a high or low number of “criteria” (i.e., approaches such as school meals and direct food aid) to fight hunger. To assess the effect of this distinction, repeated measures ANOVAs were applied for the various GHI scores and outcomes for a selection of representative years. To reveal any differences between the years, a post hoc analysis was conducted using Bonferroni correction. The findings suggest that (i) the rate of change for a country’s GHI score and other examined indicators depends upon its developmental level, and (ii) there is a direct relationship between the hunger-management model and the level of hunger in developing countries.